2022
DOI: 10.5812/aapm.123357
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral and Lateral Views: Analysis of the Technical Aspects of Spinal Cord Stimulator Lead Insertion

Abstract: Background: Spinal cord stimulation (SCS) is an established treatment modality for neuropathic pain. The critical part of this technique is safe access to the epidural space for lead placement. There have been innovations in radiological views, improving access to the epidural space. Objectives: This study analyzes the adoption of these technical advantages in daily practice Methods: We conducted a survey of members in the Spine Intervention Society and American Society of Regional Anesthesia in regard to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additional investigations further validated that this view is efficient and reliable in visualizing the needle tip in relation to the epidural space at T1 with close inter‐observer agreement and little physician instruction 21 . A recent survey of interventional pain physicians found that for epidural access during SCS lead insertion, up to 90% used the lateral view, and 65% used the CLO view 22 . However, a fluoroscopic view to determine needle tip depth, whether lateral or CLO was used by only 45%–60% of respondents during needle placement.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additional investigations further validated that this view is efficient and reliable in visualizing the needle tip in relation to the epidural space at T1 with close inter‐observer agreement and little physician instruction 21 . A recent survey of interventional pain physicians found that for epidural access during SCS lead insertion, up to 90% used the lateral view, and 65% used the CLO view 22 . However, a fluoroscopic view to determine needle tip depth, whether lateral or CLO was used by only 45%–60% of respondents during needle placement.…”
Section: Discussionmentioning
confidence: 95%
“…21 A recent survey of interventional pain physicians found that for epidural access during SCS lead insertion, up to 90% used the lateral view, and 65% used the CLO view. 22 However, a fluoroscopic view to determine needle tip depth, whether lateral or CLO was used by only 45%-60% of respondents during needle placement. The lack of consistent use of fluoroscopy to assess needle depth and the partial adoption of the CLO view may also stem from the lack of "real-world" data that supports that a particular fluoroscopic view may change clinical outcomes.…”
Section: Lateral Fluoroscopic View Onlymentioning
confidence: 99%
“…Lidocaine (5 mm) was injected to provide local anesthetic into the target area before a spine needle was introduced. A contralateral oblique image was utilized for safety and reliability [ 4 , 5 ]. After obtaining a loss of resistance with approximately 3 cm of needle insertion, iohexol contrast without additives was injected and demonstrated minimal cephalic spread (Figure 1 ).…”
Section: Case Presentationmentioning
confidence: 99%